Extensive intraperitoneal lavage to eliminate intraperitoneal tumor cells in gastrectomy with D2 lymphadenectomy for gastric cancer - Ronellenfitsch, Ulrich; Marx, Alexander; Kienle, Peter; Post, Stefan; Nowak, Kai (Tumori journal, 2018)
Introduction:Survival in gastric cancer is often limited by peritoneal carcinomatosis, which supposedly develops from serosal tumor infiltration or tumor cell spread during gastrectomy with lymphadenectomy. To eliminate peritoneal tumor cells, extensive intraperitoneal lavage (EIPL) has been suggested. Impressive results have been achieved in Japanese trials. In this trial, we assessed EIPL in Western patients.Methods:This prospective trial included patients with non-metastatic gastric adenocarcinoma undergoing gastrectomy with D2 lymphadenectomy. Peritoneal fluid samples at laparotomy, after lymphadenectomy, and after EIPL were analyzed for tumor cells using cytology and EpCAM antibodies. The primary endpoint was peritoneal conversion rate (PCR; proportion of patients in whom EIPL eliminated tumor cells after lymphadenectomy). Secondary endpoints were peritoneal release rate (PRR; proportion of patients with peritoneal tumor cells after gastrectomy/lymphadenectomy among all patients without cells before gastrectomy/lymphadenectomy) and prevalence of peritoneal tumor cells before resection. EIPL was considered ineffective if PCR ? 0.2 and warranted further exploration if PCR ? 0.5. Clinicaltrials.gov identifier is NCT01476553.Results:The trial was stopped early because tumor cells after gastrectomy/lymphadenectomy were detected in only 3/27 (11.1%) patients. In none of these did EIPL eliminate tumor cells (PCR 0, 95% confidence interval [CI] 0%?12.5%). In 8/27 (29.6%) patients, tumor cells were detected after EIPL. PRR was 11.1% (95% CI 2.4%?29.2%). There were no perioperative complications higher than Clavien-Dindo grade 3a.Conclusions:In Western patients, free peritoneal tumor cells after gastrectomy with D2 lymphadenectomy for gastric cancer were detected only sporadically. Although based on few cases, the findings suggest that EIPL spreads tumor cells into the peritoneal cavity, thus being potentially harmful. Therefore, EIPL cannot be generally recommended.
Gesehen am 11.04.2019